The impact of factors within the work environment on perceptions of training transfer : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Weir, Keryn (Massey University, 1999)
The current study was designed to investigate empirically the direct effects of various components of the work environment on perceptions of training transfer. The influence of social support from four organisational constituents (peer support, subordinate support, supervisor support, and top management support), organisational commitment and task constraints in the work environment and training transfer were evaluated. The sustained use of trained skills was also considered in the current study. Differences in perceptions of training transfer two weeks and twelve weeks after training were measured, as were the impact of each of the independent variables at each timepoint. The data was examined using correlation analyses and regression modeling. Results indicated that there were no significant differences in perceived training transfer between the time periods, but different variables were identified as important at each timepoint. Two weeks after training, top management support and organisational commitment explained 32.4 percent of the variance. Twelve weeks after training, organisational commitment was the only significant variable, explaining 31.1 percent of the variance. Results indicated some support for a positive relationship between social support and transfer. Two weeks after training, there was a relationship between transfer and supervisor support, top management support and peer support. Twelve weeks after training, the only relationship was between transfer and subordinate support. There was no relationship between task constraints and perceived training transfer. The implications of these results are discussed in relation to previous research as well as practical implications for organisations and training practitioners.
Keywords: Transfer of training; Occupational training